(untitled) (Conference Zone, 2022)
In pedagogical higher educational institutions, there are different approaches to improving the quality of training students for professional activity in the context of modern market relations. At the same time, the need to create didactic conditions that create motivation for personal development in the learning process is clearly visible. The essence of the teaching profession is determined through the activities of the person who carries it out. This activity consists in the transfer by the older generation of the culture and experience of mankind to the younger generation, creating conditions for the personal development of the younger generation, preparing it for the fulfillment of certain social tasks in society.